Covalent modification of exfoliated fluorographite with nitrogen functionalities1. Issue 29 (7th August 2015) - Bosch-Navarro, Concha; Walker, Marc; Wilson, Neil R.; Rourke, Jonathan P.
<x xml:space="preserve">Abstract</x> Chemical functionalization of exfoliated fluorographite with amino groups induces a change in the solubility properties and allows further decoration with gold nanoparticles.